Analisis Kelayakan Investasi Pada Industri Kecil Dan Menengah Di Bandung - Wawat Setiawati (Universitas Muhammadiyah Mataram, 2021)
Small and medium industries (IKM) have an important role in the Indonesian economy and in Bandung it is one of the most developed sectors. However, not all SME businesses can survive and develop in a sustainable manner. Therefore, analysis of investment feasibility is very important for IKM business actors in Bandung. In this study, various aspects that need to be considered in conducting an investment feasibility analysis are discussed, including market analysis, financial analysis, technical analysis, and risk analysis. It is hoped that this research can provide guidance for IKM business actors in Bandung to carry out an appropriate and comprehensive investment feasibility analysis, so that their businesses can survive and develop in a sustainable manner. Based on the results of the analysis, it can be concluded that investing in most SMI businesses in Bandung is feasible. However, it is necessary to pay attention to the factors that influence investment feasibility in order to minimize risk and increase investment success.